Microalgae cryopreservation techniques: choosing cryoprotectants and cooling regimens - Chernobai, Nadiia; Gerilovych, Anton; Shevchenko, Nadiia (Problems of Cryobiology and Cryomedicine, 2026)
This review was aimed to summarize and array current methods to cryopreserve microalgae, particularly, the approaches to selecting cryoprotectants and optimal cooling parameters, aimed at preserving their viability and functional activity after thawing. The paper analyses the key aspects of cryopreservation of microalgae, including the efficiency comparison of different classes of cryoprotectants as well as their impact on cells; mechanisms of cryodamage and strategies for minimizing it; optimal cooling and warming regimens for various types of microalgae. Special attention has been paid to the dependency of cryopreservation efficiency on the concentration and composition of cryoprotective solutions, which vary depending on the specific species and cultures. Some microalgae has been noted to maintain high viability using elevated concentrations of non-penetrating cryoprotectants. The necessity for further research using new and combined cryoprotective solutions has been emphasized to expand the possibilities of long-term storage of microalgae. Probl Cryobiol Cryomed. 2026; 36(1): 5—15